Podoplanin expressing macrophages and their involvement in tertiary lymphoid structures in mouse models of Sjögren’s disease - Hovd, Aud-Malin Karlsson; Nayar, Saba; Smith, Charlotte G.; Kanapathippillai, Premasany; Iannizzotto, Valentina; Barone, Francesca; Fenton, Kristin Andreassen; Pedersen, Hege Lynum (Frontiers in Immunology, 2024)
Tertiary lymphoid structures (TLSs) are formed in tissues targeted by chronic inflammation processes, such as infection and autoimmunity. In Sjögren's disease, the organization of immune cells into TLS is an important part of disease progression. Here, we investigated the dynamics of tissue resident macrophages in the induction and expansion of salivary gland TLS.We induced Sjögren's disease by cannulation of the submandibular glands of C57BL/6J mice with LucAdV5. In salivary gland tissues from these mice, we analyzed the different macrophage populations prior to cannulation on day 0 and on day 2, 5, 8, 16 and 23 post-infection using multicolored flow cytometry, mRNA gene analysis, and histological evaluation of tissue specific macrophages. The histological localization of macrophages in the LucAdV5 induced inflamed salivary glands was compared to salivary glands of NZBW/F1 lupus prone mice, a spontaneous mouse model of Sjögren's disease.The evaluation of the dynamics and changes in macrophage phenotype revealed that the podoplanin (PDPN) expressing CX3CR1+ macrophage population was increased in the salivary gland tissue during LucAdV5 induced inflammation. This PDPN+ CX3CR1+ macrophage population was, together with PDPN+CD206+ macrophages, observed to be localized in the parenchyma during the acute inflammation phase as well as surrounding the TLS structure in the later stages of inflammation. This suggests a dual role of tissue resident macrophages, contributing to both proinflammatory and anti-inflammatory processes, as well as their possible interactions with other immune cells within the inflamed tissue. These macrophages may be involved with lymphoid neogenesis, which is associated with disease severity and progression.In conclusion, our study substantiates the involvement of proinflammatory and regulatory macrophages in autoimmune pathology and underlines the possible multifaceted functions of macrophages in lymphoid cell organization.